Prevalens ketidakselesaan Muskuloskeletal (msd discomfort) dalam Kalangan anggota polis trafik di Sabah - Bernadette Thien; Peter Voo Su Kiong; Ismail Maakip (ResearchGate, 2022)
The job sector that is said to be related to the MSD problem is those who work as police officers. Studies on the prevalence rate of MSD are still not carried out in Malaysia, therefore the awareness of the effects and consequences of MSD is not well known. This study aims to examine the prevalence and gender differences in MSD among traffic police officers. This study was conducted using a cross-sectional design through a survey method using a questionnaire. A total of 262 respondents participated in this study among traffic police officers and members who carry out traffic control duties. The MSD prevalence rate for traffic policemen in the last 6 months was 96.6% with 83.6% of male traffic policemen and 13% of female policemen. The study found no significant relationship (p >.05) between the MSD prevalence rate and gender. The prevalence level for pain in the body part is 26.3% (N=69) in the neck/shoulder part, 14.5% (N=38) in the hand/finger part, 16.8% (N=44) in the arm, 30.1% (N=79 ) in the mid to lower back and 29% (N=76) in the hips/back, calves/legs. Therefore, this study is expected to provide information on the MSD prevalence rate among traffic police members as a reference to improve the level of health in their work.